Strategi Koping Masyarakat Jawa di Masa Pandemi COVID-19 - Faruq Faruq; Hanum Midya Syahrina; Nureyzwan Sabani; Siti Rahmawati; Laksmy Dewi Sukmakarti; Nanik Prihartanti (Institut Seni Indonesia Denpasar, 2022)
The COVID-19 pandemic or in Javanese terms